Pengaruh Sikap Profesional Guru Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Selfina Sari, Ahmad Jauharudin (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2019)
The teacher's professional attitude is the pattern of teacher behavior in understanding, living, and practicing the attitude of ability and professional attitude. Thus a teacher can be an example for students, and make students have success in learning. As for the problem in this study is how is the professional attitude of Islamic Religious Education teachers in Kebonsari II Public Elementary School Cilegon ?, how are the student learning outcomes in Islamic Religious Education subjects at SDN Kebonsari II Cilegon ?, and how does the teacher's professional attitude influence student learning outcomes Islamic Education in SDN Kebonsari II Cilegon? While the purpose of this study was to determine the professional attitude of Islamic Religious Education teachers at SDN Kebonsari II Cilegon, to determine student learning outcomes in Islamic Religious Education subjects at SDN Kebonsari II Cilegon, to determine the effect of teacher professional attitudes on student learning outcomes in Education subjects Islam. This research uses a descriptive method with a quantitative approach. Data collection techniques were carried out by observation, interviews, and questionnaires. The population and sample are 47 students in Kebonsari II Elementary School Cilegon with 47 students. The conclusion obtained from the results of this study is based on correlation analysis using person Product Moment (rxy), the results obtained r = 0.92 this shows that between the variables X with Y there is a very high correlation, furthermore, the correlation significance test results show that t arithmetic = 15.82 and t Table = 2.021 where t arithmetic = (15.82)> t Table = (2,021), the interpretation is that there is a significant positive correlation between the influence of the teacher's professional attitude (Variable X) with student learning outcomes ( Variable Y). The contribution of Variable X to Variable Y by using the Coefficient of Determination (CD) is 84.64%, while the remaining 15.36% is influenced by other factors.